Best Answer

9z + 10 - 6z = 7 + 2z - 3

gather together z terms on the left

3z + 10 = 7 + 2z - 3

gather integers on the right

3z + 10 = 2z + 4

subtract 2z from each side

z + 10 = 4

subtract 10 from each side

z = - 6

----------------check in original equation

9(- 6) + 10 - 6(- 6) = 7 + 2(- 6) - 3

- 54 + 10 + 36 = 7 - 12 - 3

- 8 = - 8

--------------checks

Q: How do you solve 9z plus 10-6z equals 7 plus 2z-3?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

Related questions

Try listing with Century 21-Island Realty 98 West Street, Corner Brook, NL A2H 2Z3, Canada- (709) 637-2111